Alcohol Use Disorders Identification Test (AUDIT) scores are elevated in antipsychotic-induced hyperprolactinaemia - Lawford, B.; Barnes, M.; Connor, J.; Heslop, Karen; Nyst, P.; Young, R. (Sage Publications, 2012)
Hyperprolactinaemia in antipsychotic treated patients with schizophrenia is a consequence of D2 receptor (DRD2) blockade. Alcohol use disorder is commonly comorbid with schizophrenia and low availability of striatal DRD2 may predispose individuals to alcohol use. In this pilot study we investigated whether hyperprolactinaemia secondary to pharmacological DRD2 blockade was associated with alcohol use disorder in 219 (178 males and 41 females) patients with schizophrenia. Serum prolactin determinations were made in patients diagnosed with schizophrenia and maintained on antipsychotic agents. Clinical assessment included demographics, family history and administration of the AUDIT (Alcohol Use Disorders Identification Test). Higher AUDIT scores were associated with prolactin-raising antipsychotic medication (n = 106) compared with prolactin-sparing medication (n = 113). Risperidone (n = 63) treated patients had higher AUDIT scores and prolactin levels than those on other atypical antipsychotics (n = 113). Across the entire sample, patients with a prolactin greater than 800 mIU/L had higher AUDIT scores and were more likely to exceed the cut-off score for harmful and hazardous alcohol use. These differences were not explained by potential confounds related to clinical features and demographics, comorbidity or medication side-effects. These data suggest that by lowering dosage, or switching to another antipsychotic agent, the risk for alcohol use disorder in those with schizophrenia may be reduced. This hypothesis requires testing using a prospective methodology.